Connecting the Different Lexical Category Domains: Cognition in the Zero Derivation of Adjectives from Nouns in Macedonian - Marjana Vaneva (European Scientific Journal, ESJ, 2019)
Cognition is a basis of cognitive linguistics and a driving force in the noun to adjective zero-derivation. By expanding the meaning of the first lexeme, cognition enables the speaker to derive a new lexeme, and empowers the hearer to understand the semantics of the newly zero-derived element. The paper studies the process of noun to adjective zero-derivation through cognition. It studies the semantic similarity between the same-form lexemes – the source and the target lexeme, which belong to different lexical categories, one is a noun and the other is an adjective, in the case when cognition and association links enable the process of zero-derivation to take place. The research method applied here is that Macedonian nouns are taken, compared to Macedonian adjectives with the same form, but similar meaning, when it is exactly the similarity in meaning that is studied, actually, the speaker’s and hearer’s motivation to zero-derive an adjective from a noun. The conclusion of the paper notes that the morphological identity (derivationally) and the semantic similarity (through cognition), between the two lexemes in Macedonian, can be accompanied by inflectional suffixes for number, definiteness and gender - modifications that can be made to both lexemes. Consequently, the natural-class noun from the left is zero-derived into an adjective on the right, when, in most cases of this kind of zero-derivation, it appears in, what is originally, a two-noun phrase, in which the second remains to be a noun, while the first becomes a zero-derived adjective.